Methodology of Teaching Physics at the Requirement of International Assessment Programs (Pisa) (Journal of Pedagogical Inventions and Practices, 2023)
The article tells about the worldwide educational program PISA, about the purpose, functions, systematic composition and directions of the program. It is considered in what forms of training the implementation of the educational program is organized and what results are obtained from this program, how the PISA program is monitored.